Erving Goffman’s Frame Analysis as a Life Coaching Theoretical Orientation as Implemented through Frame Coaching - LeBlanc, Bruce (Technium Social Sciences Journal, 2021)
Within the field of coaching psychology and life coaching tension exists regarding the use of proprietary psychological methods with clinical and counseling psychologists. Such tensions can result in charges of practicing psychology without a license. Consequently, appropriate alternative methods need to be explored and developed. When developing these methods, alternative theoretical orientations should be utilized. One such theoretical orientation is Erving Goffman’s Frame Analysis, a social psychological approach to examining human behavior. This article proposes Goffman’s Frame Analysis as an alternative theoretical orientation for undertaking life coaching within coaching psychology. Frame Coaching is utilized as the life coaching method to support Frame Analysis.